HUBUNGAN TINGKAT KONSUMSI KALSIUM, MAGNESIUM, STATUS GIZI (IMT/U), DAN AKTIVITAS FISIK DENGAN KRAM PERUT SAAT MENSTRUASI PRIMER PADA REMAJA PUTRI (STUDI DI SEKOLAH MENENGAH ATAS KESATRIAN 2 KOTA SEMARANG TAHUN 2017) - Novalia Clara Rosvita; Laksmi Widajanti; Dina Rahayuning Pangestuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Stomach cramps during primery menstruation is a pain or cramps in the lower abdomen which occurs before, and during menstruation. Suspected factors of the stomach cramps during menstruation are stress, hormone, some nutrients, and physical activity. The purpose of the research was to analyze the correlation of, consumption level of calcium, magnesium, nutritional status and physical activity with stomach cramps during primery menstruation in Kesatrian 2 Senior High School Semarang City 2017. This was a quantitative research with cross sectional design. Data of calcium and magnesium intake was collected using Food Frequency Semi Quantitative form, data of the stomach cramps during menstruation was using Numeric Rating Scale. Population of this research were 112 teenage girls. Research samples were 52 teenage girls who met the inclusion criteria. Sampling technique was using purposive sampling. Data was analyzed using Chi Square test. The results showed that Level of CalciumConsumption was classified as deficit (82,7%). Level of Magnesium Consumption was classified as deficit (51,9%). Nutritional status was not risky (69,2%). Physical Activity was risky (61,5%). As many as 76.9% of teenage girls experience stomach cramps during menstruation. Statistical results showed that there was a correlation of level of calcium consumption with stomach cramps during primery menstruation (p = 0,022), there were no correlation of level of magnesium consumption (p = 0,072), nutritional status (p = 0,478), and physical activity (p = 1,00)with stomach cramps during primery menstruation. This research recommended to increase nutritional intake as recommended or according to body needs and reduce doing heavy phyisical activity to reduce the pain during menstruation.